Awareness of HIV and prevention of parent-to-child transmission among antenatal mothers, Solur, Magadi Taluk, Ramnagara district, Karnataka - Kallumkal, Mia George; Joseph, Merlyn; Bijoy, Riya; George, Mekha Jude; Yao, Ogul; Doss, Archana; Johnson, Avita Rose (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Globally, 4,30,000 children aged under 15 years were infected with HIV in 2008. Most of the cases were reported in developing countries, of which more than 90 percent are the result of mother-to-child transmission during pregnancy, labour and delivery or breast feeding. Parent-to-child transmission accounts for about 4.3 percent of the overall HIV transmission in the country. This study was conducted to assess the awareness of HIV and its vertical transmission in pregnancy and its determinants among pregnant women availing care at a rural maternity hospital in Karnataka. Methods: A hospital-based cross-sectional study in Ramnagara district, in which 231 pregnant women were recruited by consecutive sampling and administered a face-validated structured questionnaire. A 55-item questionnaire to assess awareness about HIV and prevention of parent to child transmission was administered. Women were given knowledge scores based on answers to the questionnaire and women securing more than 70% of the total score, were considered to have good awareness. Results: The study population included 132 (57%) primigravida. The mean age of the study population was 23.8±3.67 years. Among the study participants, only 93 (42%) women were aware of vertical transmission of HIV-AIDS. Awareness regarding HIV in pregnancy was found to be significantly associated with type of family (p=0.024) and age of study participant (p<0.002). Conclusions: Awareness regarding prevention of HIV-AIDS and parent-to-child transmission of HIV-AIDS among antenatal mothers is poor. A significant association was found between type of family and age of study participant and knowledge regarding HIV-AIDS among the study participants. This can be improved by addressing different myths and misconceptions regarding transmission of HIV in routine health education programmes.